Voltammetric Investigation of Iron(III) Interactions with Phytate. (10th September 2015) - Marolt, Gregor; Šala, Martin; Pihlar, Boris
Graphical abstract: ABSTRACT: The electrochemical behavior of Fe(III) in the presence of phytate ligand was investigated by cyclic voltammetry on the polycrystalline gold and mercury drop electrodes in the pH range between 1.5 and 10, and ligand to metal molar ratio from 0 to 20. Complexation of Fe(III) and Fe(II) by phytate ligand (L) reflects in (i) shift of the formal potential E 0′ of the Fe(III)/Fe(II) redox couple into the negative direction, and (ii) an increased irreversibility of the redox processes. Change of the formal potential originate from higher stability of the Fe(III)L complex with respect to Fe(II)L complex, however, due to the slow charge transfer control of the redox processes apparent stability constants calculated from voltammetric data may lead to an overestimation of their true values. Irreversible reduction of Fe(III)L to Fe(II)L is diffusion controlled and involves one proton per one electron on both electrodes. Reduction of Fe(III) phytate complex to Fe(II)L depends on the pH and at pH < 5 proceeds via [Fe III H5 L] 4– species, but at higher pH less protonated [Fe III H3 L] 6– become the major reacting species. An almost stepwise change of the reduction peak potential for more than 0.8 V into the negative direction around pH 5 indicate that both reactants have quite different stability and/or structure. We predicted that electronic configuration and affinity of Fe(III) ions for the octahedral coordination induce the inversion of phytate ligand from its equatorial to the axial conformation which form more than ten orders of magnitude more stable Fe(III)L complexes. Fe(II)L intermediate generated on the electrode is strongly adsorbed on both gold and mercury electrodes, and totally irreversible reduction of Fe(II)L complex to the Fe metal was observable at mercury electrode as well. From Fe(III/II)L peak analysis on the mercury electrode the cathodic charge transfer coefficient of 0.68 was found, for [Fe III H3 L] 6– reacting species the diffusion coefficient of (9.1 ± 0.1) × 10 −7 cm 2 /s was estimated, and the rate constant k 0 of 7.8 × 10 −5 cm/s was calculated.